Exploring Key Growth Drivers and Strategies for Enhancing Performance of Indian Food Tech Startups - Munshi, Angad; Singla, Ashim Raj (Indian Journal of Marketing, 2022)
The startup food tech business is a promising option due to its massive size and high repeat ordering behavior, besides the high margins emanating from it. Thus, to remain competitive and factor sustainability, the sector needs to revisit strategies, more so post 2019 due to the challenges posed by the COVID-19 pandemic. It is time to focus on the adoption of strategic options for improving the performance of startup food tech platforms while taking cognizance of various critical growth drivers. This paper explored the key growth drivers and challenges startup food tech platforms face and suggested strategies for enhancing their performance. The empirical study was undertaken using a fully structured questionnaire to collect data from the delivery staff of startup food tech platforms in seven major cities in India. The primary data thus collected was used for the descriptive analysis based on the respondents' demographic information. Confirmatory factor analysis (CFA) was carried out to support construct validation to assess the validity of the survey items based on the overall fitness of the model. Structural equation modeling (SEM) was used to test the hypothesized relationships between latent factors. The key growth drivers and their corresponding impact on other variables were worked out. This study recommended innovative strategies that can make the food delivery business more successful. The finding revealed that the key growth drivers included personalization & focused marketing, quality assurance, extended convenience, and value to consumers, and their corresponding strategies were reconnoitered. The paper would aid the concerned food tech sector further develop and implement strategic options for enhancing its business performance